Studi Kualitas Fisik Udara Dan Sanitasi Dasar Di Ruang Tunggu Pelabuhan Tenau Dan Pelabuhan Bolok - Olga Mariana Dukabain; Onesimus Numba (JURNAL INFO KESEHATAN, 2017)
The problem of air supply and the lack of sanitation facilities in the seaport waiting room is still a problem, including in the waiting room of Tenau Port and Bolok Port, this can be shown by many passengers who feel hot and hot, a lot of garbage is scattered, the number of latrines is lacking and there are puddles water in front of the toilet. This study aims to determine the temperature, humidity, ventilation, velocity of air flow, quantity of clean water, latrines, trash cans, sewerage. This research is a descriptive study that describes the results of field observations and data that have been obtained during the study to obtain deeper facts about the physical quality of air and basic sanitation. The subject of this study is the waiting room of Tenau Port and Bolok Port.